WANN HÄTTE MAN EINEM EIN BAD ZURICHTEN KÖNNEN? ZU PROZESSEN DER ENTSTEHUNG UND DES SCHWUNDES VON REDENSARTEN - Komenda-Earle, Barbara (Proverbium - Yearbook, 2012)
The paper discusses the idiomatic paradigm of the German proverbial expression jdm. ein Bad zurichten which includes the formal, se-mantic and cultural analysis of idioms and proverbs with the same figurative meaning. The diachronic analysis starts from the oldest collocations and phrases with the component Bad like jdm. das Bad aufgießen, jdm. ein Bad rüsten/bereiten/ zurichten etc. and shows their development in meaning and form from the beginning (15th century) till nowadays. The most important mechanism of the semantic changes are metonymy and metaphor, the formal factors are the lexical exchange of the verbal component, the reduction of the lexical variations and the context of use. The paradigm shows a high liveliness from the start till nowadays. Despite passing of the proverbial expressions jdm. ein Bad zurichten, jdm das Bad (ge)segnen new units like baden gehen, das Bad in der Menge, ein Bad in der Menge nehmen appearing show the agility of the paradigm and mean its revitalization.